2017
DOI: 10.1371/journal.pone.0171248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biogas sparging on the performance of bio-hydrogen reactor over a long-term operation

Abstract: This study aimed to enhance hydrogen production from sugarcane syrup by biogas sparging. Two-stage continuous stirred tank reactor (CSTR) and upflow anaerobic sludge blanket (UASB) reactor were used to produce hydrogen and methane, respectively. Biogas produced from the UASB was used to sparge into the CSTR. Results indicated that sparging with biogas increased the hydrogen production rate (HPR) by 35% (from 17.1 to 23.1 L/L.d) resulted from a reduction in the hydrogen partial pressure. A fluctuation of HPR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This variation of the HRT shifted the metabolism to favor the HY (5.73 mmol H 2 /g COD). Although H 2 does not participate in the production of succinic acid [Equation ()], substrate competition between both routes may result in a lower HY 50 7normalC6H12O6+6CO212CH4H6O4+6normalH2normalO ΔG0=119.280.12emkJ/mol …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation of the HRT shifted the metabolism to favor the HY (5.73 mmol H 2 /g COD). Although H 2 does not participate in the production of succinic acid [Equation ()], substrate competition between both routes may result in a lower HY 50 7normalC6H12O6+6CO212CH4H6O4+6normalH2normalO ΔG0=119.280.12emkJ/mol …”
Section: Resultsmentioning
confidence: 99%
“…This caused an increase in lactic acid concentration from 24 to 1038 mg COD/L in the author's study. Although H 2 is not produced or consumed in the conversion of glucose to lactic acid [Equation (3)], substrate competition between these pathways results in lower HY values, 50 as observed in the production of succinic acid. On the other T A B L E 3 Comparison between the HSu yields of the reactors in the present study and those in the literature using pure cultures…”
Section: Fermentative Performance Of the Afbrsmentioning
confidence: 99%
“…Sparging biogas from the CH 4 stage, which mainly consisted of CO 2 and CH 4 , could reduce the H 2 partial pressure in the H 2 stage and thus improve the H 2 yield [90][91][92][93]. On the other hand, it was observed that injection of CO 2 into the H 2 stage of a pilot-scale twostage system increased VFA production [94], which might lead to pH drop and unstable H 2 production.…”
Section: Biogas Recirculationmentioning
confidence: 99%
“…Apart from the mentioned 1G and 2G wastes, there are some intermediate substrates produced in sugarcane processing industry which can be used for two-stage AD processes, like crushed cane (2G) and sugar syrup (1G). Very few studies have been carried out using these wastes [106,107].…”
Section: Energy Balance Of Single-stage Vs Two-stage Anaerobic Digest...mentioning
confidence: 99%